2021
DOI: 10.48550/arxiv.2105.11558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-optimal Offline and Streaming Algorithms for Learning Non-Linear Dynamical Systems

Abstract: We consider the setting of vector valued non-linear dynamical systems X t+1 = φ(A * X t ) + η t , where η t is unbiased noise and φ : R → R is a known link function that satisfies certain expansivity property. The goal is to learn A * from a single trajectory X 1 , • • • , X T of dependent or correlated samples. While the problem is well-studied in the linear case, where φ is identity, with optimal error rates even for non-mixing systems, existing results in the non-linear case hold only for mixing systems. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…By contrast, previous work assumes i.i.d. data or focuses on either linear models [Simchowitz et al, 2018, Tsiamis and Pappas, 2019, Jedra and Proutiere, 2020 or parametric models with known nonlinearities , Sattar and Oymak, 2020, Jain et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, previous work assumes i.i.d. data or focuses on either linear models [Simchowitz et al, 2018, Tsiamis and Pappas, 2019, Jedra and Proutiere, 2020 or parametric models with known nonlinearities , Sattar and Oymak, 2020, Jain et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is well-known that this dependency can be avoided for learning in linear systems [Lai andWei, 1982, Simchowitz et al, 2018]. Recently Jain et al [2021] showed under a strong invertibility condition that dependency on the mixing time can also be avoided for the generalized linear model ( 16). This leaves open the question whether learning without mixing is possible in situations beyond the generalized linear model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations